Structure and variability of antarctic circumpolar current in the Indian Ocean sector [electronic resource] - Toh, Hai Jian, 1989-, author (2013)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2013